Security aspects in cloud based condition monitoring of machine tools - Tedeschi, Stefano; Mehnen, Jorn; Tapoglou, Nikolaos; Roy, Rajkumar (Elsevier, 2015)
In the modern competitive environments companies must have rapid production systems that are able to deliver parts that satisfy highest quality standards. Companies have also an increased need for advanced machines equipped with the latest technologies in maintenance to avoid any reduction or interruption of production. Eminent therefore is the need to monitor the health status of the manufacturing equipment in real time and thus try to develop diagnostic technologies for machine tools. This paper lays the foundation for the creation of a safe remote monitoring system for machine tools using a Cloud environment for communication between the customer and the maintenance service company. Cloud technology provides a convenient means for accessing maintenance data anywhere in the world accessible through simple devices such as PC, tablets or smartphones. In this context the safety aspects of a Cloud system for remote monitoring of machine tools becomes crucial and is, thus the focus of this paper
Keywords: Cloud; Remote Maintenance; Machine Tool; Secure Communications; Remote Monitoring